Optimization of groundnut shell fast pyrolysis for the production and characterization of bio-oil using fabricated fixed bed reactor - Ayodeji Rapheal, Ige; Cosmos Moki, Elinge; Muhammad, Aliyu; Muhammed, Gwani; Gusau Hassan, Lawal (International Journal of Advanced Chemistry, 2020)
Renewable plant materials are regarded as one of the most affirmative option for the production of fuels and chemicals. With the concept of pyrolysis process, there is every possibility to produce alternative sources of energy and fuels from renewable biomass. The study depicts the production, optimization and characterization of bio-oil from pyrolyzed groundnut shell using fabricated reactor. The pyrolysis process was produced with bio-oil response, bio-char response and non condensable gases response as products. The effect of pyrolysis variables were observed by the production of the bio-oil as the response. Sixty runs of pyrolysis experiments were suggested by box Benkhen design indicated optimum pyrolysis condition at particle size of 1.15mm mesh, reaction time of 83 mins and temperature of 650oC. The maximum bio-oil yield was obtained with 33.91% at optimum condition. The bio-oil samples had better performance which met the specifications for the measured properties and compares well with the ASTM standard. Therefore, using groundnut shell for bio-oil production via pyrolysis process can serve as an approach of providing a sustainable alternative source of fuel and friendly environment.Â Â